Efektivitas Regulasi Perlindungan Konsumen dalam Penanganan Investasi Bodong: Analisis Kasus Doni Salmanan - Nailul Inayah; Nurul Ilmiah; Pandu Abdillah Samari; Putri Setiyo Lestari; Emma Yunika Puspasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the effectiveness of consumer protection regulations in handling fraudulent investments, focusing on the case of Doni Salmanan, a social media influencer involved in illegal investment promotion. Fraudulent investments have become a serious threat to society in Indonesia, especially in the context of the development of digital technology that allows the rapid dissemination of information. This research uses a normative legal research method with a case study approach, examining applicable regulations such as Law Number 8 Year 1999 on Consumer Protection and regulations of the Financial Services Authority (OJK). The results of the analysis show that although there are existing regulations to protect consumers, the implementation and supervision of illegal investment activities are still weak. Weak supervision, low public financial literacy, and inadequate sanctions against fraudulent investment actors indicate the need to update and strengthen regulations. This study provides recommendations to improve the effectiveness of consumer protection regulations and build more adaptive mechanisms to prevent investment fraud in the digital era.